Phosphate-solubilizing bacteria will not significantly remobilize soil cadmium remediated by weathered coal - Gao, Qiong; Li, Qu-Sheng; He, Bao-Yan; Yang, Jun-Qing; Wang, Li-Li; Wang, Jun-Feng; Jiang, Jian-Jun; Wang, Dong-Sheng; Wang, Yi-Fan (Environmental science and pollution research international, 2019)
Cadmium (Cd) re-mobilize by phosphate-solubilizing bacteria (PSB) from immobilization contaminated soil has drawn great attention due to its serious threat to human health through food chain. However, Cd binding with weathered coal (WC), an effective Cd immobilization material, will be re-mobilized by PSB or not is still unclear. In this study, the soil and sand pots with Cd were respectively mixed with the weight fractions of 0‰, 2‰, and 3‰ WC, inoculated with or without PSB, and planted with Amaranthus mangostanus L. The experimental results indicated that: (i) Cd in soil was transformed into organic fraction with WC, which has been led to the Cd accumulation concentrations in roots and shoots reduced by 38.8% and 20.5%, respectively; (ii) PSB could promote the concentration of exchangeable-Cd fraction and soil Cd uptake by amaranth in all treatments; and (iii) WC application in sand pot respectively reduced the Cd accumulation by 47.5% in roots and 24.1% in shoots, but PSB inoculation showed no significant effect on Cd accumulation in plants under WC application. SEM, zeta potential, and FT-IR results showed that PSB inoculation after Cd immobilized by WC had no influence on the microstructure, amount of negative charge, type, and content of functional groups in WC, indicating that organic fraction Cd in WC was not re-mobilized by PSB. Therefore, the application of WC in contaminated soil was conducive to transforming Cd in organic-bound forms and intensifying Cd immobilization effects.